Rethinking Halal Marketing: Emerging Opportunities and Future Challenges in the Global Marketplace - Rustam Rustam; Nuryanti; Haniah Lubis (Indonesian Journal of Islamic Literature and Muslim Society, 2026)
This study analyzes the development of halal marketing within the globalization of the halal industry and proposes a reconstructed, adaptive, integrative, and comprehensive paradigm to address contemporary market challenges. Using a qualitative approach, this research conducts a critical review of 213 scholarly works related to halal marketing and the halal industry. The findings reveal a significant shift in the marketing paradigm from product- and customer-oriented approaches toward value-based marketing. In this context, halal is no longer understood merely as normative compliance, but as a value system that integrates religion, ethics, transparency, trust, and sustainability. However, its implementation faces several challenges, including low halal literacy, a certification-oriented understanding of halal, fragmented standards, changing consumer behavior, and the demands of digital transformation. This study proposes a reconstructed halal marketing paradigm consisting of three key dimensions: halal values, market dynamics, and marketing strategy. The proposed framework positions halal marketing as a holistic system that creates economic, social, ethical, and sustainable value. This study contributes to the advancement of halal marketing theory in global business contexts.